The Cost of Safety: Cost Analysis Model - Behm,Michael; Veltri,Anthony; Kleinsorge,Ilene (Professional Safety, 2004)
Knowledge in business and accounting helps SH&E professionals speak to management and maintain credibility. To work more effectively with other financial and operations management personnel, SH&E professionals must become better versed in the common language of business. Cost analysis models are needed to help SH&E professionals measure, analyze and communicate safety strategies in business terms. This article details one such model from the quality management literature.
Keywords: Accounting

Topic presentation on entrepreneurship in Oregon and how the OSU-COB is key to economic development in the state - Dowling,Thomas; Kleinsorge,Ilene (Oregon in Business Conference, 2003)
Keywords: Accounting; Management; Strategy & Entrepreneurship

Using total quality processes and learning outcome assessments to develop management curricula - Drexler,John; Kleinsorge,Ilene (Journal of Management Education, 2000)
A process was designed to identify what total quality skills should be included in the authors curriculum and howto deliver them. Customer data led the authors to change their focus toward exploring and assessing what they do in the entire curriculum. The emphasis on learning outcomes is a theme in American Assembly of Collegiate Schools of Business and education reform. The authors summarize things learned that may help others avoid certain pitfalls and build on the authors progress to date.
Keywords: Accounting; Management

A Benchmarking Study of the Current Practices with Regard to the Role of the Quantitative Curriculum in Business Schools - Kleinsorge,Ilene (International Journal of Operations and Quantitative Management, 1997)
Keywords: Accounting

Lessons Learned Using Total Quality Concepts for Accounting Curriculum Development - Kleinsorge,Ilene (1997)
Keywords: Accounting

Linking Accounting Courses with an Unstructured Project - Kleinsorge,Ilene (1997)
Keywords: Accounting

A Multicourse Practice Set: The Ultimate 'Messy' Problem - Kleinsorge,Ilene (Journal of Private Enterprise, 1997)
Keywords: Accounting

Financial and Efficiency Differences in Family-Owned and Non-Family Owned Nursing Homes An Oregon Study - Kleinsorge,Ilene (Family Business Review, 1994)
Keywords: Accounting

Perceptual Measures of Quality: A Tool to Improve Nursing Home Systems - Koenig,Hal; Kleinsorge,Ilene (Hospital & Health Services Administration, 1994)
Keywords: Accounting; Marketing

TQM: Are Cost Accountants Meeting The Challenge - Kleinsorge,Ilene (Management Accounting, 1994)
Keywords: Accounting

The Silent Customers: Measuring Customer Satisfaction in Nursing Homes - Koenig,Hal; Kleinsorge,Ilene (Journal of Health Care Marketing, 1991)
This article presents a research which focuses on customer satisfaction in the health care industry, which has recently shown a heightened awareness of and new interest in quality issues. The research was conducted within a regulated business sector and nursing homes. The purpose of our research is to assist an administrator in such an effort by developing a customer satisfaction survey that could be used by nursing home administrators to measure, on an ongoing basis, the satisfaction of both the nursing home residents and the family members, appointed custodians and concerns friends (FCFs). Focus groups were used to identify quality/satisfaction dimensions from the perspective of nursing home residents and FCFs, these are a cost efficient way to solicit information from participants. Using the participants' statements, we developed statements related to the six dimensions. Four of the dimensions pertain to groups in the home: nurses and aides, administrators, dietary, and housekeeping. The fifth dimension is the amount of empathy exhibited by the staff and the final dimension pertains to a variety of issues related to the home environment. As a result of the licensing power of the state, the ultimate consumers (residents) and FCFs are commonly overlooked. Often nursing home administrators become so caught up in trying to satisfy the state that the satisfaction of the ultimate customers goes unmeasured and in many instances is ignored.
Keywords: Accounting; Marketing